Ensaio de síntese crítica acerca do Cretácico terminal e do Paleogénico de Portugal - Antunes, M. Telles (2008)
A synthetic essay about portuguese Late Cretaceous (Upper Campanian-Maastrichtian) and Paleogene is presented. This does include most of the so far known data, a critical approach to the problems of such formations, and to previous works on them. Our viewpoints (party original) are exposed in a shorter text in French where most of the discussion was suppressed (see reference in Resumo).